SOME FEATURES OF THE AGROCHEMICAL COMPOSITION OF THE SOILS OF THE WESTERN POLISSYA OF UKRAINE - Лисиця, Андрій (SWorldJournal, 2023)
The results of the study and analysis of the chemical composition of the soils of the Western Polissya of Ukraine are presented in this work. This region includes the northern regions of Rivne and Volyn’ regions. We characterized the geographical and ecol